Vulcanization and antioxidation effects of accelerator modified antioxidant in styrene-butadiene rubber: Experimental and computational studies. (July 2020) - Luo, Kaiqiang; Ye, Xin; Zhang, Hao; Liu, Jingya; Luo, Yanlong; Zhu, Jing; Wu, Sizhu
Abstract: In this work, a new kind of accelerator modified antioxidant denoted as BTC was synthesized successfully through a thiol-ene click reaction between accelerator 2-mercaptobenzothiazole (MBT) and antioxidant N-(4-anilino phenyl) maleic imide (MC). Then, the effects of BTC on the vulcanization and antioxidation of styrene-butadiene rubber (SBR) were comprehensively studied via experimental and computational methods. It was discovered that BTC not only reduced the negative effect of MC on the vulcanization of SBR composite but also accelerated the vulcanization reaction. Besides, the aromatic amino and thioether groups in BTC played a crucial role in improving the thermo-oxidative aging resistance of SBR composites. Moreover, as against MBT or MC, BTC with a high molecular weight, amorphous state, and low solubility parameter exhibited lower migration and better dispersion in the SBR matrix. Therefore, in contrast to MBT/SBR or MBT/MC/SBR composite, BTC/SBR composite manifested an optimal overall performance, i.e., high vulcanization efficiency, outstanding mechanical properties, and good thermo-oxidative stabilization. These results indicated that BTC could be used as a prospected multifunctional additive to fabricate the high-performance SBR composites. Furthermore, molecular simulation as a useful tool can offer valuable theoretical guidance for the molecule design of high-efficiency antioxidants. Highlights: A new accelerator modified antioxidant BTC was prepared by a thiol-ene reaction. BTC could act as an accelerator to promote the vulcanization reaction of SBR. BTC greatly improved the thermo-oxidative aging resistance of SBR composites. The effects of BTC on antiaging of SBR were deeply studied by molecular simulation.